2017
DOI: 10.1093/ee/nvx126
|View full text |Cite
|
Sign up to set email alerts
|

Plant Flavonoid Content Modified by Domestication

Abstract: Plant domestication can modify and weaken defensive chemical traits, reducing chemical defenses in plants and consequently their resistance against pests. We characterized and quantified the major defensive flavonols and isoflavonoids present in both wild and cultivated murtilla plants (Ugni molinae Turcz), established in a common garden. We examined their effects on the larvae of Chilesia rudis (Butler) (Lepidoptera: Arctiidae). Insect community and diversity indices were also evaluated. We hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
0
16
1
Order By: Relevance
“…Results on the flavonol content in murta fruit have been inconsistent. In one study, no significant differences between wild and cultivated murta fruits were found [44,45]. Conversely, in another study by Augusto [40], the total phenolic compounds in the fruits of wild and selected murta (14-4) genotype were 19.4 and 40.3 mg GAE/g in dry weight, respectively.…”
Section: Genotype Vs Environmentmentioning
confidence: 89%
“…Results on the flavonol content in murta fruit have been inconsistent. In one study, no significant differences between wild and cultivated murta fruits were found [44,45]. Conversely, in another study by Augusto [40], the total phenolic compounds in the fruits of wild and selected murta (14-4) genotype were 19.4 and 40.3 mg GAE/g in dry weight, respectively.…”
Section: Genotype Vs Environmentmentioning
confidence: 89%
“…In berries, high antioxidant activity is most often associated with berries from wild species, together with a broad variety of anthocyanins and high total polyphenol contents compared to cultivated varieties. In commercial cultivars, the flavonoid content has often been altered and reduced during domestication with an accompanying increase in susceptibility towards pests/insects [99]. In this study, we investigated a wide range of wild and cultivated berry fruit species representing diverse plant families (Berberidaceae, Caprifoliaceae, Elaeocarpaceae, Ericaceae, Grossulariaceae, Rosaceae and Myrtaceae) to provide a broad platform for classification of genes and their products and to establish fruit-specific expression patterns to gain new insights into the complex regulation of metabolic pathways during berry fruit development.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study on mutants of poplar trees, silenced in the cinnamyl-Co reductase ( CCR ) gene of the monolignol-specific lignin pathways, showed significant effects on the density and composition of culturable rhizosphere and endosphere bacteria, microbiome shifts that were proposed to be mediated, at least in part, by changes in extractable plant phenolic compounds such as ferulic acid [ 27 ]. In this context, it is worth noting that one of the most common domestication syndrome traits is related with the changes in the type and amount of secondary metabolites, such as the loss of specific compounds that are toxic for humans or livestock or the reduction of flavonoid content in the leaves [ 28 30 ]. To date, however, very little is known about the qualitative and quantitative differences between root exudation profiles of crop plants and their wild relatives.…”
mentioning
confidence: 99%